(untitled) (Research, Society and Development, 2021)
The present study aimed to extract and evaluate the antimicrobial and cytotoxic potential of alkaloid-rich fractions obtained from Mitracarpus frigidus aerial parts. The isolation of alkaloids was performed by acid-base extraction and column chromatography with Sephadex LH-20 as stationary phase. The antimicrobial activity was evaluated by the broth microdilution method to determine the minimum inhibitory concentration (MIC) and also by antimicrobial quantitative parameters (total activity, percentage of activity and microbial susceptibility index) against nine strains of microorganisms: Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella typhimurium, Shigella sonnei, Klebsiella pneumoniae, Escherichia coli, Bacillus cereus, Candida albicans and Cryptococcus neoformans. Cytotoxicity was tested against Artemia salina and two leukemic cell lines, HL60 and Jurkart. The fraction richest in alkaloid showed expressive activity for S. aureus, S. typhimurium, B. cereus, P. aeruginosa, S. sonnei and C. neoformans with MIC below 0.100 mg/mL. The samples did not show cytotoxic effect against A. salina and, in relation to the tumor cell lines, only the fractions rich in alkaloids showed moderate activity with about 50 and 35% decrease in cell viability for HL60 and Jurkart, respectively. The presented results open perspectives for the future isolation, purification and identification of bioactive substances from M. frigidus that can be used, mainly in the treatment of microbial infections.